Dispersion of Switching Processes in Ferroelectric Ceramics - O. V. Malyshkina; Anton Yurievich Eliseev; R. M. Grechishkin (Advances in Condensed Matter Physics)
The influence of the switching processes on self-heating of ferroelectric PZT ceramics samples was studied in high-amplitude sine and meander electric fields in a wide frequency range of 50 to 1500 Hz. It is shown that the linear dependence of the self-heating temperature on the electric field frequency is observed only in low-frequency region. It was found that there exists a maximum on the frequency dependence of the self-heating temperature. The critical frequency fcr corresponding to this maximum depends on both the properties of the material and geometry of the sample.